(untitled) (Journal of Partial Differential Equations, 2019)
In this study, first we give some conditions to prove that a fractional Burgers equation has a unique solution. For this aim, we define a special operator to deduce the uniqueness of the solution. Then we prove that the optimal control problem under fractional Burgers equation has at least one optimal solution.